Emerging bacterial and fungal pathogens in healthcare and the threat of drug resistance - Alzahrani, Khaled Swailem; Almutairi, Khulood Majed; Alsulami, Afaf Wazin; Aseeri, Abdulrhman Mohmmed; Alqarni, Mohammed Ahmed; Haffah, Arwa Ahmad; Alqahtani, Muhannad Fahad; Almistadi, Mohammed Fahad; Muaddi, Saad Ali Bin; Ayoub, Hanin Abdulrahman (International Journal Of Community Medicine And Public Health, 2023)
Managing the treatment of fungal infections, in healthcare facilities is extremely important as drug resistance continues to rise. It’s crucial to have programs that oversee the use of antibiotics which can help reduce the emergence of resistance. Rapid diagnostic tools like polymerase chain reaction and next generation sequencing (PCR and NGS) are helpful in targeting treatment plans. Implementing rigorous infection control protocols can effectively reduce the transmission of infections, within healthcare facilities. Collaborative efforts between specialists ensure customized treatment plans that address resistance profiles. Combating evolving drug resistance involves approaches such as combination therapy and immunotherapies. Educating healthcare workers and patients about infection prevention and control is essential. Surveillance and epidemiology play a role in tracking resistance patterns, which in turn guide interventions. International cooperation is crucial due to travel patterns. Continuous research and innovation are essential for management providing insights into treatment effectiveness and mechanisms of resistance. The clinical implications of drug resistance such as increased severity, treatment failures and limited options underscore the need, for an approach. In conclusion, it is imperative to have clinical management strategies to tackle the challenges posed by emerging drug pathogens while safeguarding patient outcomes and public health.